Gestalt und Eigenschaften der Extremalfunktionen in einigen linearen und nichtlinearen Aufgaben - Terpigoreva, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Терпигорева. Вид и свойства экстремальных функций в некоторых линейных и нелинейных экстремальных задачахV. Terpigoreva. Kai kurie tiesiniai ir netiesiniai ekstremumo uždaviniai; ekstremalinių funkcijų pavidalas ir savybės